Aprender a aprender: uma trajetória possível para os trabalhadores do SUS? - Costa, Ana Clara Lopes (Universidade Federal de São Carlos, 2014)
The main goal in this study is to analyze the learning process of the Brazilian Unified Health System (SUS) staff when exposed to an interactionist educational initiative. Such initiative aims the transformation of health practices by focusing on clinical management and qualifying care for the users of SUS in 33 hospitals from the 5 Brazilian geographical regions. This study used a specialization course that was developed in 2009-10 that focused on the articulated development of management abilities, support and education in health. The study was based on the principles of qualitative research and the completion of course work drawn by the attendees of the specialization course on Clinical Management was also used as a source of data. The content was analyzed for data interpretation aiming to identify and explain the causes and interactions for the production of the phenomenon. The novelty of the proposal was not an obstacle for the learning process. Student focused learning and the appreciation of previous knowledge where related to the practical application of such content and the broaden of autonomy, especially on what concerns recently acquired information. It was also observed that the participants actions were related to the three areas: clinical management; health awareness and education. The interaction in small groups, communication, integration and open dialogue were valued as fundamental e facilitating elements of learning, group work development and qualification of care. Transformation on practices on health related to management, attention and education were observed and were part of the knowledge that define the profile of clinical management built and developed through the course.
Keywords: Trabalho; Aprendizagem baseada em problemas; Governança clínica; Work; Problem-based learning; Clinical governance; CIENCIAS DA SAUDE